Novel splice-site and missense mutations in the ALDH1A3 gene underlying autosomal recessive anophthalmia/microphthalmia. Issue 6 (25th February 2014) - Semerci, C Nur; Kalay, Ersan; Yıldırım, Cem; Dinçer, Tuba; Ölmez, Akgün; Toraman, Bayram; Koçyiğit, Ali; Bulgu, Yunus; Okur, Volkan; Şatıroğlu-Tufan, Lale; Akarsu, Nurten A
Abstract : Aim: This study aimed to identify the underlying genetic defect responsible for anophthalmia/microphthalmia. Methods: In total, two Turkish families with a total of nine affected individuals were included in the study. Affymetrix 250 K single nucleotide polymorphism genotyping and homozygosity mapping were used to identify the localisation of the genetic defect in question. Coding region of the ALDH1A3 gene was screened via direct sequencing. cDNA samples were generated from primary fibroblast cell cultures for expression analysis. Reverse transcriptase PCR (RT-PCR) analysis was performed using direct sequencing of the obtained fragments. Results: The causative genetic defect was mapped to chromosome 15q26.3. A homozygous G>A substitution (c.666G>A) at the last nucleotide of exon 6 in the ALDH1A3 gene was identified in the first family. Further cDNA sequencing of ALDH1A3 showed that the c.666G>A mutation caused skipping of exon 6, which predicted in-frame loss of 43 amino acids (p.Trp180_Glu222del). A novel missense c.1398C>A mutation in exon 12 of ALDH1A3 that causes the substitution of a conserved asparagine by lysine at amino acid position 466 (p.Asn466Lys) was observed in the second family. No extraocular findings—except for nevus flammeus in one affected individual and a variant of Dandy–Walker malformation in another affected individual—were observed. Autistic-like behaviour and mental retardation were observed in three cases. Conclusions: In conclusion, novel ALDH1A3 mutations identified in the present study confirm the pivotal role of ALDH1A3 in human eye development. Autistic features, previously reported as an associated finding, were considered to be the result of social deprivation and inadequate parenting during early infancy in the presented families.